An Evaluation of the Management of Solid Waste in the Town of Limbe and Buea: Non-Legal Measures - Eboa, Ehabe Samuel (Law and Economy, 2025)
This study critically evaluates the management of solid waste in the towns of Limbe and Buea, Cameroon, with a specific focus on non-legal measures. The increasing volume of solid waste in these urban centers, driven by rapid urbanization, population growth, and changing consumption patterns, poses significant environmental, public health, and aesthetic challenges. While legislative frameworks exist at national and municipal levels to address waste management, their implementation has been largely insufficient, prompting the need to examine alternative or complementary strategies outside the legal domain. The research investigates the effectiveness of non-legal measures—such as public awareness campaigns, community-based initiatives, educational programs, private sector participation, informal sector involvement, and the role of non-governmental organizations (NGOs)—in promoting sustainable waste management practices. A mixed-methods approach was adopted, combining field observations, unstructured interviews of stakeholders, and secondary data analysis to assess how these measures are operationalized in both towns. Findings reveal that while the legal infrastructure remains underutilized, non-legal interventions have played a crucial role in mitigating waste-related issues. Community mobilization efforts in neighborhoods, school-based sensitization campaigns, and partnerships with waste collection firms have yielded varying degrees of success in improving waste disposal habits and reducing environmental degradation. However, the study also uncovers critical limitations such as poor coordination among stakeholders, inconsistent funding, limited technical expertise, and a lack of long-term strategic planning. The research concludes that although non-legal measures cannot fully substitute for robust legal enforcement, they provide essential and often more adaptable mechanisms to engage communities and stakeholders in waste management. It recommends a hybrid approach that strengthens these grassroots initiatives while simultaneously improving the legal and institutional frameworks to foster a more sustainable and inclusive waste management system in Limbe and Buea.